1995
DOI: 10.1111/j.1600-0528.1995.tb00250.x
|View full text |Cite
|
Sign up to set email alerts
|

Subjective and objective orthodontic treatment need among orthodontically treated and untreated Finnish adolescents

Abstract: Subjective orthodontic treatment need was studied in a sample of 340 Finnish adolescents with and without previous orthodontic treatment. The subjects, who were attending two schools preparing students for college, first filled in a questionnaire. Of the 340 subjects, 24.4% of the treated and 24.0% of the untreated expressed subjective orthodontic treatment need (NS). For the clinical examination, 110 subjects were systematically sampled from four groups; subjects who had received orthodontic treatment in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 32 publications
1
13
1
Order By: Relevance
“…When only those studies using the DHC were compared, the frequency of treatment need in the present population was higher than those reported for Finns [ 21 , 23 ] and Kuwaiti citizens [ 25 ], but smaller than that reported for male Asians [ 15 ] and Saudi citizens [ 33 ]. (Table 4 ) Different selected sample sizes and age ranges within the evaluated young adults might have contributed to the reported differences in normative orthodontic treatment need.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…When only those studies using the DHC were compared, the frequency of treatment need in the present population was higher than those reported for Finns [ 21 , 23 ] and Kuwaiti citizens [ 25 ], but smaller than that reported for male Asians [ 15 ] and Saudi citizens [ 33 ]. (Table 4 ) Different selected sample sizes and age ranges within the evaluated young adults might have contributed to the reported differences in normative orthodontic treatment need.…”
Section: Discussioncontrasting
confidence: 61%
“…Previous studies in young adults indicated that normative orthodontic treatment need ranged from 1.4% to 71.6% [ 15 , 17 - 28 , 33 ]; however, different indexes were used in the studies (Table 4 ). Some of these studies have even included young adults with a history of previous orthodontic treatment [ 18 , 20 , 21 , 25 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors exclude them (11-13), while others include them (14-16). In the present study, patients receiving orthodontic treatment at the time of examination were excluded and those who had received orthodontic treatment in the past were included.…”
Section: Discussionmentioning
confidence: 99%
“…Need for orthodontic treatment based on indexes has normally been higher compared to the individuals' perception of their treatment need. [5][6][7][8] Thus, need for treatment according to indexes is not necessarily the determinant of orthodontic treatment and an individual's perception of the dentofacial complex as well as psychological need for orthodontic treatment are of greater importance. Overall, treatment can be affected more by demand rather than need.…”
Section: Introductionmentioning
confidence: 99%